Optimal network reconfiguration and distributed generation sizing with consideration of protection system / Mohamad Norshahrani Abdul Rahim - Mohamad Norshahrani , Abdul Rahim (2020)
Research on network reconfiguration (NR) considering distributed generation (DG) commonly focus on the issues of power loss, voltage deviation, DG sizing and its placement. These works are important and required in the planning stage of the distribution networks. In most of the past works, the protection system is neglected in this stage although it is essential to prevent the network from damages during operation. Without proper consideration of protection system settings and coordination during NR, the protection system may operate inaccurately. This happens due to changes in current flow and fault level when the network changes its configuration. As a result, the distribution system with new configuration may fail to be protected when a fault occurs. In order to avoid this problem, this study proposes optimal NR for distribution networks connected with DG with consideration of the protection system. Due to the high capital cost of setting a new protection scheme, reconfiguration without changing the existing protection schemes is mostly preferred by the network operator. Therefore, this research aims to find the optimal configuration which provides minimum power loss, optimal DG sizing and at the same time ensuring existing protective settings unaffected by the network reconfiguration and DG operation. The optimization of NR and DG sizing is formulated simultaneously in consideration of the application for normal condition, fault condition and restoration. Meanwhile, the protection system settings are incorporated as constraints in the optimization process. In this research, the considered protection devices are overcurrent relay, recloser and fuse. In order to further improve the power loss reduction and voltage profile, the fuses are replaced with overcurrent relays. To ensure minimum operating time, the relay time multiplier setting (TMS) is optimized. The effectiveness of the proposed method is analyzed on IEEE 33-bus, IEEE 69-bus and IEEE 118-bus distribution system. The obtained results demonstrate that NR without considering the protection system settings will lead to failure in the protection distribution system. Despite higher power loss of 11.4% to 25.8% as compared to the configuration without considering protection constraint, the proposed method able to ensure the protection system is working accurately. Based on the results, it can be observed that with the consideration on protection constraints, the proposed method manage to improve the network's performance of 33-bus, 69-bus and 118-bus by 55.1%, 43.5%, and 49.2% of power loss reduction respectively compared to the power loss in the initial configuration.